PENGARUH PERBEDAAN HABITAT KELAPA SAWIT (Elaeis guineensis Jacq.) TERHADAP KELIMPAHAN MUSUH ALAMI ULAT API (LEPIDOPTERA : PSYCHIDAE) - Yusmaidar Sepriani (UNIVERSITAS LABUHANBATU, 2018)
One of the important pests attacking coconut palm is Ulat Pemakan Daun Kelapa Sawit (UPDKS) like the Caterpillar. The management of habitat can be done with clean cultivation practices or cultivation use nuts cover soil (cover crop) to increase natural enemies. The research was carried out in April until July 2017. The purpose of this study was to know the abundance of natural enemies population Caterpillar fire contained in research. The location of the research consists of a private plantation with a cover crop and land communities without a cover crop. Observations of the Caterpillar's fire done every week, from first week to third week. The observation is done by swiping pitfall trap method and net. Each block palm oil taken 5 plot used to sweep net and each plot placed 2 pitfall trap. The abundance of natural enemies population level Caterpillar fires on plantation with a cover crop of 137 individuals. The community's land without a cover crop of 107 individuals. Natural enemies was found in the predator type of land cover crop as much as 88% and natural enemies of type parasitoid as much as 12%. Predator type natural enemies present on the land without a cover crop as much as 99% and parasitoid type of natural enemies as much as 1%. Keywords: caterpillar, natural enemies, palm oil, parasitoid, predator